Atypical adenoma of the thyroid diagnosed as anaplastic cancer by cytopathology. Issue 10 (22nd May 2017) - Hatakeyama, Hiromitsu; Hoshino, Kimiko; Mizoguchi, Kenji; Suzuki, Takayoshi; Hatanaka, Kanako C.; Yamaya, Yukie; Kano, Satoshi; Mizumachi, Takatsugu; Homma, Akihiro
Abstract : Atypical adenoma of the thyroid is a rare form of tumor, and its accurate diagnosis prior to surgical resection is difficult as the histological and pathological morphologies are very similar to those of anaplastic thyroid carcinoma (ATC), and its anaplastic transformation remains to be elucidated. We reported a case of a 75‐year‐old female with a thyroid isthmus nodule diagnosed repeatedly by FNAC as anaplastic carcinoma. Both the first and second FNAC specimen slides showed a large number of scattered or aggregated atypical cells consisting of large, pleomorphic nuclei with irregular membranes, chromatin clumps and prominent nucleoli. The morphology of the surgical specimen was similar to that of an anaplastic carcinoma and although it showed signs of transition from a normal follicular epithelium, there was no invasive growth or mitosis. This lesion was diagnosed as an atypical adenoma, and a papillary carcinoma was also present in the right lobe of the thyroid. Here we evaluate the molecular features of atypical adenomas in comparison with 9 ATC samples, and discuss whether or not atypical adenomas represent a form of premalignant lesion. Ki‐67 expression was found to be very low in atypical adenomas whereas all ATC samples showed high levels of Ki‐67 expression. Epithelial–mesenchymal transition (EMT) marker expression suggested that atypical adenomas maintain their epithelial phenotype to a higher degree than do ATCs. Differential diagnosis between ATC and atypical adenoma is difficult by cytological and histological methods alone, and Ki‐67 and EMT marker expression may support the diagnosis.